miRNA Landscape in Pathogenesis and Treatment of Vogt–Koyanagi–Harada Disease - Vega-Tapia, Fabian; Bustamante, Mario; Valenzuela, Rodrigo A.; Urzua, Cristhian A.; Cuitino, Loreto (Frontiers in Cell and Developmental Biology, 2021)
miRNAs, one of the members of the noncoding RNA family, are regulators of gene expression in inflammatory and autoimmune diseases. Changes in miRNA pool expression have been associated with differentiation of CD4+ T cells toward an inflammatory phenotype and with loss of self-tolerance in autoimmune diseases. Vogt–Koyanagi–Harada (VKH) disease is a chronic multisystemic pathology, affecting the uvea, inner ear, central nervous system, and skin. Several lines of evidence support an autoimmune etiology for VKH, with loss of tolerance against retinal pigmented epithelium-related self-antigens. This deleterious reaction is characterized by exacerbated inflammation, due to an aberrant TH1 and TH17 polarization and secretion of their proinflammatory hallmark cytokines interleukin 6 (IL-6), IL-17, interferon γ, and tumor necrosis factor α, and an impaired CD4+ CD25high FoxP3+ regulatory T cell function. To restrain inflammation, VKH is pharmacologically treated with corticosteroids and immunosuppressive drugs as first and second line of therapy, respectively. Changes in the expression of miRNAs related to immunoregulatory pathways have been associated with VKH development, whereas some genetic variants of miRNAs have been found to be risk modifiers of VKH. Furthermore, the drugs commonly used in VKH treatment have great influence on miRNA expression, including those miRNAs associated to VKH disease. This relationship between response to therapy and miRNA regulation suggests that these small noncoding molecules might be therapeutic targets for the development of more effective and specific pharmacological therapy for VKH. In this review, we discuss the latest evidence regarding regulation and alteration of miRNA associated with VKH disease and its treatment.